On the lumber industry: Ethical concerns as the other side of profits - Hoch, David (Journal of business ethics, 1994)
The collusive relationship between the U.S. Forest Service and the lumber industry substantially harms the public interest, and inspires Congressional clearcutting and stumping policies. An anthropocentric1 (or homocentric) culture milieu fosters destruction of America's old growth forests which results in ethically-relevant questions. It is proposed that corporate moral responsibility be extended to indirect stakeholders and that a transcendent environmental ethic, biocentrism2 (or deep ecology), oblige management to expand the sphere of external stakeholders to include environment objects such as animals, trees, and biotic communities.